Full in-vitro analyses of new-generation bulk fill dental composites cured by halogen light - YILMAZ ATALI, PINAR (ELSEVIER SCIENCE BV, 2017)
The objective of this study was to investigate the full in-vitro analyses of new-generation bulk-fill dental composites cured by halogen light (HLG). Two types' four composites were studied: Surefill SDR (SDR) and Xtra Base (XB) as bulk-fill flowable materials; QuixFill (QF) and XtraFill (XF) as packable bulk-fill materials. Samples were prepared for each analysis and test by applying the same procedure, but with different diameters and thicknesses appropriate to the analysis and test requirements. Thermal properties were determined by thermogravimetric analysis (TG/DTG) and differential scanning calorimetry (DSC) analysis; the Vickers microhardness (VHN) was measured after 1,7, 15 and 30 days of storage in water. The degree of conversion values for the materials (DC, %) were immediately measured using near-infrared spectroscopy (FT-IR). The surface morphology of the composites was investigated by scanning electron microscopes (SEM) and atomic-force microscopy (AFM) analyses. The sorption and solubility measurements were also performed after 1, 7, 15 and 30 days of storage in water. In addition to his, the data were statistically analyzed using one-way analysis of variance, and both the Newman Keuls and Tukey multiple comparison tests. The statistical significance level was established at p < 0.05. According to the ISO 4049 standards, all the tested materials showed acceptable water sorption and solubility, and a halogen light source was an option to polymerize bulk-fill, resin-based dental composites. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Dental; Bulk fill resin composite; Flowable; Packable; In-vitro analyses; Halogen light; RESIN-BASED COMPOSITES; MECHANICAL-PROPERTIES; WATER SORPTION; DIMETHACRYLATE RESINS; FLEXURAL STRENGTH; BOND STRENGTH; POLYMERIZATION; RESTORATIONS; SOLUBILITY; CONVERSION